BIOLOGICAL AND ECOLOGICAL CHARACTERISTIC OF BADGERS IN THE CHECHEN REPUBLIC - Hussein Junuzovic Andrianov; Aslanbek Magomedovich Bakiev (Юг России: экология, развитие, 2015)
The article presents the results of long-term observations of the hunting-fishing kind of fauna of the CR - Badger. Studied feeding habits, reproduction, placement, as well as the influence of various factors on the strength and survival of the species. The study tested many modern methods of surveillance and data processing on many issues of biology and ecology of the species in all natural zones of the Republic.Methods: we used the methods of collecting faeces and traces of life, taking the number on the analysis of havens, accounting tracks. The feeding habits have been studied on the contents of stomachs and defining systematic conditioning food residue. Applied techniques Morphometry, morphological and physiological analysis.Results: the results of the research were obtained data on abundance and Habitat Badgers in the Chechen Republic, on the number of species in different natural zones. Describe the basic biology and ecology of the species, its morphological and physiological indicators. Describes in detail the feeding habits and reproduction of Badger in the foothills and high mountains, the influence of anthropogenic factors.Application results: the data obtained by environmental organizations for the development of measures to protect the species from poachers and illegal methods of extraction. Results of the study of biology and ecology can be used to analyze the influence of characteristics of natural and climatic conditions of the Chechen Republic to the environmental adaptation of species, assessing the practical value of Badgers in the wild.